Click‐Connected 2‐(Hydroxyimino)aldehydes for the Design of UV‐Responsive Functional Molecules. Issue 2 (16th December 2020) - D'Acunzo, Francesca; Carbonaro, Linda; Cort, Antonella Dalla; Di Sabato, Antonio; Filippini, Dario; Leonelli, Francesca; Mancini, Laura; Gentili, Patrizia
Abstract: Click chemistry is used to functionalize simple lipophilic and water‐soluble molecules, a complex PEGylated phospholipid (DSPE‐PEG2000), and two benzylic substrates with the 2‐(hydroxyimino)aldehyde (HIA) group. To this end, two terminal alkynes bearing the HIA moiety were synthesized and coupled to different azides through copper(I)‐catalyzed azide alkyne cycloaddition (CuAAC). Norrish–Yang photoisomerization (λ= 365 nm, LED source) is successfully obtained, with no interference by the triazole linker, except when the forbidden n‐π* carbonyl transition is screened by a remote substituent such as salicylaldehyde. UV‐Vis spectrometry suggests a specific interaction of HIAs with Cu(II), whereas no such evidence is found with Cu(I). We thereby show that the CuAAC methodology can be used successfully to obtain HIA‐based UV‐responsive hydrophilic or lipophilic ligands, phospholipidic components for the construction of liposomes, and macrocycle precursors. Abstract : The 2‐(hydroxyimino)aldehyde (HIA) group undergoes Norrish–Yang photoisomerization to ciclobutanol oxime and is under investigation as metal ions ligand. Herein, click chemistry was used as a straightforward procedure to obtain HIA‐based functional molecules, the products obtained by UV irradiation with a LED source (λ=365 nm) were characterized and it was shown by UV‐Vis spectrometry that HIAs specifically interact with Cu(II).